Purification and Catalytic Upgrading of Bio-Based Oils to Sustainable Aviation Fuel - Selimi, Jon ; 0009-0003-8260-9353 (Department of Process and Life Science Engineering, Lund University., 2025)
The global aviation industry is experiencing growing pressure to decarbonize, driving significant demand for Sustainable Aviation Fuel (SAF). Second-generation feedstocks that do not directly compete with food crops, such as lipid oils from insects and lignin-derived oils, are promising sources, but their high concentrations of inorganic contaminants and oxygen make them incompatible with existing refinery infrastructure and downstream processes. This thesis assesses a three-step upgrading route for converting bio-based oils to jet-fuel-like hydrocarbons. The first step addressed feedstock purity by applying a water-free ion-exchange treatment to Black Soldier Fly Larvae (BSFL) lipids, where Amberlyst 15 at 75 °C removed over 99% of calcium without altering the oil’s bulk properties, highlighting its potential to protect downstream units from contamination. The second, central step focused on hydrodeoxygenation (HDO). For BSFL lipids, a parametric HDO study in a batch reactor achieved complete deoxygenation. Additionally, oil yield increased with temperature and pressure, giving the highest values above 370 °C and 50 bara. Increased stirring improved yields at lower temperatures and above 600 rpm helped overcome mass-transfer limits, with diminishing effect when exceeding 60 bara. Catalyst loading raised yield at lower temperature but promoted cracking at higher temperature. Complementary continuous experiments investigated wetting and hydrogen-supply effects using indicator ratios, showing that low liquid hourly space velocity (LHSV) of 0.5 1/h with moderate-to-high H2/oil ratios of ≥ 800 mL/mL improved liquid-film coverage and favored the HDO pathway over decarboxylation/decarbonylation. To improve robustness in HDO, a two-layer graded catalyst system was implemented for esterified lignin oil to manage high reactivity and mitigate coke formation. Continuous operation was sustained for 600 h at industrially relevant LHSV of 0.8 1/h, with modest pressure-drop growth and high hydrocarbon yield, demonstrating stable long-run behavior and complete deoxygenation. Furthermore, co-processing a petroleum fraction such as vacuum gas oil with BSFL lipids enhanced efficiency and stability. Analysis of CO2, CO, and H2O indicated shifts toward HDO at suitable blend levels, consistent with improved dilution, hydrogen solubility, and controlling of exothermic heat. The final conditioning step involved hydroisomerization of the deoxygenated BSFL oil to produce a product with a chemical profile tuned to more closely align with SAF specifications. Using 0.5% Pt/Y-zeolite at 350 °C and 30 bara increased isoparaffins from 12.1% to 29.2% and reduced olefins to 0.2%.
Keywords: second-generation feedstock; lipid oil; lignin oil; purification; ion exchange; hydrodeoxygenation; hydroisomerization; sustainable aviation fuel